Embryotoxicity of atrazine and its degradation products to early life stages of zebrafish (Danio rerio) - Blahová, Jana; Cocilovo, Claudia; Plhalova, Lucie; Svobodova, Zdenka; Faggio, Caterina (Environmental toxicology and pharmacology, 2020)
Triazine herbicide atrazine is considered to be moderately toxic to various aquatic animals. The aim of our study was to evaluate the acute embryotoxicity of atrazine and its two degradation products, desisopropylatrazine and desethylatrazine, and their mixture to the early life stages of zebrafish (Danio rerio) by means of a modified method of the Fish Embryo Acute Toxicity (FET) Test - OECD guideline 236. Toxic effects were studied by the evaluation of lethal endpoints and development of disorders. Furthermore, sublethal endpoints such as hatching rate, formation of somites, development of eyes, spontaneous movement, heartbeat, blood circulation, pigmentation and occurrence of edema at 24, 48, 72 and 96 h post fertilization were assessed. Newly fertilized eggs were exposed to various concentrations of atrazine, desisopropylatrazine and desethylatrazine, and their combination 0.3, 30, 100, 300, 1000, 3,000 and 10,000 μg/l, which represent environmentally relevant levels of these pollutants in surface waters and multiples of these concentrations to find out if the toxic effect depends on dose. Single substances and their combination were not associated with a negative effect on mortality. Rare malformations were observed during these embryonal toxicity tests. Only pericardial edema was recorded during the monitored observation. A significant increase in the occurrence of pericardial edema between the control 0% and the experimental group 17.6 %) was found only in the group exposed to the highest concentration of a triazine herbicide combination (10,000 μg/l) at 72 and 96 h post fertilization. Obtained results indicate that especially higher not environmentally relevant concentrations of atrazine, its metabolites or their combination present a potencial risk of embryotoxicity for zebrafish.
Keywords: chemické látky znečišťující vodu; Embryo, Nonmammalian; Zebrafish; Atrazine; perikard; Embryonic Development; atrazin; Water Pollutants, Chemical; dánio pruhované; Herbicides; Toxicity Tests, Acute; Pericardium; Edema; Animals; zvířata; herbicidy; embryonální vývoj; testy akutní toxicity; embryo nesavčí; edém